Character-based Class Management Strategy at Pertiwi Kindergarten DWP Wonosobo (International Journal of Education and Literature, 2025)
Character development is an important part of the learning process in AUD. The study was conducted using qualitative descriptive techniques with sources from interview results, documentation, and observation . The purpose of the study focused on the development of children's character through classroom management strategies located in Pertiwi DWP Kindergarten, Wonosobo Regency. The learning process is not limited to the level of knowledge, but is also optimal in conveying character values in AUD. The good or bad character-based classroom management has an impact on the effectiveness of character development carried out by teachers. The results of the study showed that teachers carried out classroom management strategies by setting class rules , building positive relationships , modeling good behavior, giving appreciation to children , carrying out reflection activities. Based on the results of the implementation of classroom management, teachers are able to develop positive characters, namely discipline, responsibility, empathy, honesty and self-confidence.